Reviewer acknowledgments and awards: Recognition awards for distinction of reviewing in 2024 - Flores, Paulo (2025)
In 2024, members of the Mechanism and Machine Theory journal’s Editorial Board and many independent reviewers contributed their time and expertise in reviewing manuscripts. This process greatly benefits our editors, contributing authors, and ultimately our readers. In fact, the high standard and reputation of the journal is strongly shaped by the expert knowledge, generous time contribution, and commitment to mechanism and machine science of the body of reviewers. Both, Elsevier, the publisher, and the editor-in-chief of the journal, would like to publicly pay tribute to all of the 1856 reviewers who completed a total of 4717 reviews during the year of 2024. We are extremely grateful for their outstanding contributions and we are look forward to working with them in 2025!